Analisis Penerapan Aplikasi Klampid New Generation (KNG) Dalam Mempermudah Pelayanan Kependudukan Di Kota Surabaya (Studi Kasus: Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya) - Azzahra, Risma Dhiza; Gamaputra, Gading (Universitas Negeri Surabaya, 2023)
The implementation of Electronic Government in the City Of Surabaya has been implemented by many agencies, especially the Departement Of Population and Civil Registration of the City Of Surabaya. In implementing this Electronic Government, the Surabaya City Population and Civil Registry Office has made an innovation in the form of an application called Klampid New Generation, where this application can provide benefits to facilitate the implementation of population services for the people of Surabaya City. With this application, the hope of Surabaya City population and Civil Registry Service is to create effective and efficient services. But in implementing this application there are still problmes, 1). The comunity does not understand the operation of the application, 2). There is no guidebook in application, 3). Public complaints about staff who are not yet reliable in providing information to the public. The purpose of this research is to analyze, describe the application of the Klampid New Generation. This type of research is descriptive qualitative. Source collection technique with purposive sampling, in addition, researchers use a research focus using Delone and McLean’s theory which discusses the succes of information Technology System in implementing electronic government which consists of information quality consisting of sub, information completeness, informasi accuracy, reliability, data is always updated, putput forms. Of these sub-categories, only 2 categories can be said to be good, namely in the form of output where the KNG application provides benefits to the community and employees, data and data are always updtaed properly because employees have carried out their duties to always update population data through the application provied by the ministry of home affairs. While catagories that cannot be said to be good are completeness because there is no application manual, accuracy because the nformation provided to the public is still not in accordance with the real conditions of the application, reliability, namely there are still employees who are less reliable due to the age factor and appearance of the KNG application. Keywords: Electronic Government, Klampid New Generation, Public Service